Characterization of the Phytochemical Constituents of Taif Rose and Its Antioxidant and Anticancer Activities. (27th October 2013) - Abdel-Hameed, El-Sayed S.; Bazaid, Salih A.; Salman, Mahmood S.
Abstract : Ward Taifi (Taif rose) is considered one of the most important economic products of Taif, Saudi Arabia. In this study both fresh and dry Taif rose were biologically and phytochemically investigated. The 80% methanol extracts and n -butanol fractions of dry and fresh Taif rose had high radical scavenging activity toward artificial 1, 1-diphenyl picrylhydrazyl (DPPH) radical with SC50 values range 5.86−12.24 µg/ml whereas the aqueous fractions showed weak activity. All samples had in vitro anticancer activity toward HepG2 with IC50 < 20 µg/ml which fall within the criteria of the American Cancer Institute. High positive correlation appeared between the antioxidant activity and total phenolics whereas there is no correlation between total phenolics and anticancer activity. The LC-ESI(− ve)-MS analysis of all extracts indicate the presence of phenolic compounds belonging to hydrolysable tannins and flavonol glycosides. In conclusion, the presence of this is considered to be the first phytochemical report that identifies the major compounds in dry and fresh roses using HPLC-ESI-MS. The methanol extracts and its n -butanol and aqueous fractions for both fresh and dry Taif rose could be used as preventive and therapeutic effective natural agents for diseases in which free radicals involved after more in vitro and in vivo studies.